Demanding Change of Colonial Child Protection Systems Through Good Trouble: A Community‑Based Commentary of Resistance and Advocacy - Swan, Debra; Swan, Jen (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2023)
Aboriginal and Torres Strait Islander communities, led particularly by Grandmothers and Aunties, have persistently challenged statutory child protection systems and the harms they inflict on our children, families, and communities. Reflecting on our own experiences advocating for Aboriginal families and communities at the practice and systems level, this paper explores a reflective commentary approach concerning opportunities and challenges of community-based advocacy toward substantive sustained change. We note how the voices, experiences, and expertise of Aboriginal and Torres Strait Islander people continue to be marginalised or ignored by non-Indigenous authorities, colonial systems, and practice. Despite the apologies and promises of successive governments, contemporary systems continue to reflect “past” approaches. In this context, we honour the strong women who have, and continue, to stand up for their children, families, and communities, further rallying for ongoing resistance and reform.